"For how long are we going to take the tablets?" Kenyan stakeholders' views on priority investments to sustainably tackle soil-transmitted helminths. (May 2019) - Khan, Mishal S.; Pullan, Rachel; Okello, George; Nyikuri, Mary; McKee, Martin; Balabanova, Dina
Abstract: Recent global commitments to shift responsibility for Neglected Tropical Disease (NTD) control to affected countries reflect a renewed emphasis on sustainability, away from aid-dependency. This calls for a better understanding of how domestic stakeholders perceive investments in different strategies for NTD control. Soil transmitted helminths (STH) are among the NTDs targeted for elimination as a public health problem by international agencies through mass drug administration, provided periodically to at-risk population groups, often using drugs donated by pharmaceutical companies. This study was conducted in Kenya at a time when responsibilities for long running STH programmes were transitioning from external to national and sub-national agencies. Following an initial assessment in which we identified key domestic stakeholders and reviewed relevant scientific and government documents, the perspectives of stakeholders working in health, education, community engagement and sanitation were investigated through semi-structured interviews with national level policymakers, county level policymakers, and frontline implementers in one high-STH burden county, Kwale. Our conceptual framework on sustainability traced a progression in thinking, from ensuring financial stability through the technical ability to adapt to changing circumstances, and ultimately to a situation where a programme is prioritised by domestic policymakers because empowered communities demand it. It was clear from our interviews that most Kenyan stakeholders sought to be at the final stage in this progression. Interviewees criticised long-term investment in mass drug administration, the approach favoured predominantly by external agencies, for failing to address underlying causes of STH. Instead they identified three synergistic priority areas for investment: changes in institutional structures and culture to reduce working in silos; building community demand and ownership; and increased policymaker engagement on underlying socioeconomic and environmental causes of STH. Although challenging to implement, the shift in responsibility from external agencies to domestic stakeholders may lead to emergence of new strategic directions. Highlights: Sustainability was not conceptualised as self-sufficiency to continue a programme. Mass drug administration criticised for neglecting root causes of worm infestation. Kenyan stakeholders linked sustainability to building community demand for health. Community demand was seen as a precursor to increased political attention. As Kenyan stakeholders lead on NTD control, investment strategies may change.